2022
DOI: 10.1021/acsami.2c15570
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Diammonium Directed In-Plane Charge Transport Enhancement in Two-Dimensional Lead Bromide Perovskite for Weak-Light Detection

Abstract: Two-dimensional (2D) Dion-Jacobson (DJ) perovskites are drawing significant attention in optoelectronic fields because of their enhanced out-of-plane electron coupling and improved structure stability. However, the structural effects of organic cations on the in-plane charge transport properties of 2D DJ lead bromide perovskites have remained less explored. Herein, we adopt asymmetric 3-(dimethylamino)-1-propylammonium (DMPD) and symmetric butane-1,4-diammonium (BDA) to systematically investigate the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The theoretical E g data of 3 , 5 , and 7 accord with the experimental values (Figure a,e,i). It is shown that the orbital interactions between the Pb and Br ions dominate the valence band level and a small Pb–Br octahedron distortion corresponds to a small E g . That means the D d decreases when the bridging Br ion locates near the center of adjacent Pb ions so that the Br-4p orbitals are close to the straight line connecting the adjacent Pb ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical E g data of 3 , 5 , and 7 accord with the experimental values (Figure a,e,i). It is shown that the orbital interactions between the Pb and Br ions dominate the valence band level and a small Pb–Br octahedron distortion corresponds to a small E g . That means the D d decreases when the bridging Br ion locates near the center of adjacent Pb ions so that the Br-4p orbitals are close to the straight line connecting the adjacent Pb ions.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the orbital interactions between the Pb and Br ions dominate the valence band level and a small Pb−Br octahedron distortion corresponds to a small E g . 60 That means the D d decreases when the bridging Br ion locates near the center of adjacent Pb ions so that the Br-4p orbitals are close to the straight line connecting the adjacent Pb ions. Therefore, the increased overlap of Pb-6s and Br-4p orbitals leads to a reduced E g .…”
Section: Resultsmentioning
confidence: 99%
“…49,50 In addition, the σ 0 values of the title crystals were lower than that of some 2D perovskite single crystals, such as Rb 3 Bi 2 I 9 (8.43 × 10 10 cm −2 ) 51 and (Gua) 3 Bi 2 I 9 (3.35 × 10 10 cm −2 ). 52 Also, remarkably, after Sn alloying, the μ was effectively enhanced, which should be ascribed to the likelihood that more charge carriers in the 2D perovskite were thermally activated, and a proportion of free charge was also involved. 53 Both the increased carrier mobility and decreased trap states suggest a reduced non-radiative recombination loss for the crystals, which is beneficial for photoelectric applications.…”
Section: Resultsmentioning
confidence: 98%
“…27 [DMPD is 3-(dimethylamino)-1-propylammonium], which is constructed by the asymmetric diammonium cations and delivered a detectivity of 1.73 × 10 12 Jones under a light power intensity of 0.16 mW/cm 2 . 28 Although some photodetection works based on a DJ hybrid perovskite single crystal have been reported so far, however, most reported single-crystal devices based on DJ hybrid perovskites are usually constructed by aliphatic diammonium and showed relatively poor weak light detection ability, with a detection limit of around μW/ cm 2 . 29−31 Therefore, the research on DJ hybrid perovskites constructed by aromatic diammonium used for weak light detection is still rare, especially for the photodetection at the level of nW/cm 2 .…”
mentioning
confidence: 99%
“…In addition, a bilayered DJ hybrid perovskite crystal (HDA)­CsPb 2 Br 7 (HAD is 1,6-hexamethylenediammonium) was developed by Sun’s group, who studied its photoactivities under 3 mW/cm 2 polarized light, with the detectivity of 1.5 × 10 9 Jones achieved in the crystal-based device . Recently, Chen et al reported a 2D DJ hybrid perovskite (DMPD)­PbBr 4 [DMPD is 3-(dimethylamino)-1-propylammonium], which is constructed by the asymmetric diammonium cations and delivered a detectivity of 1.73 × 10 12 Jones under a light power intensity of 0.16 mW/cm 2 . Although some photodetection works based on a DJ hybrid perovskite single crystal have been reported so far, however, most reported single-crystal devices based on DJ hybrid perovskites are usually constructed by aliphatic diammonium and showed relatively poor weak light detection ability, with a detection limit of around μW/cm 2 . Therefore, the research on DJ hybrid perovskites constructed by aromatic diammonium used for weak light detection is still rare, especially for the photodetection at the level of nW/cm 2 .…”
mentioning
confidence: 99%